Criminal Sentencing of Doctors as Perpetrators of Sexual Violence Against Patients from the Perspective of the Objectives of Punishment - Pratiwi Dwi Saputri; Hafrida; Herry Liyus (Journal of Law, Politic and Humanities, 2026)
Sexual violence committed by doctors against patients constitutes a serious criminal offense that not only violates criminal law provisions but also undermines human values, professional ethics, and public trust in healthcare services. The unequal power relations between doctors and patients place victims in a vulnerable position, thus requiring a fair, firm, and victim-oriented sentencing system. This research aims to analyze the legal regulation and application of criminal sentences for sexual violence committed by doctors against patients within the Indonesian criminal law system, as well as to formulate ideal sentencing policies for the future. The research problems are formulated as follows: (1) how are the legal regulations and implementation of sentences for sexual violence committed by doctors against patients within the Indonesian criminal law system; and (2) how should future sentencing policies for such crimes be developed from the perspective of Indonesian criminal law. This study employs normative legal research methods using statutory, conceptual, and case approaches, particularly through the analysis of Decision of the Palembang District Court Number 919/Pid.B/2024/PN Plg. The data are analyzed qualitatively using descriptive-analytical methods. The results of this study indicate that, normatively, the legal framework governing sentencing for sexual violence has been established in the Criminal Code (KUHP), Law Number 12 of 2022 concerning Sexual Violence Crimes, and other relevant regulations. However, in practice, the implementation of sentencing still faces various obstacles, particularly in terms of evidentiary challenges, unequal power relations between doctors and patients, and victims' reluctance to report due to social stigma and psychological pressure. Furthermore, the sentence imposed in court decisions has not fully reflected substantive justice, as it has not thoroughly considered the psychological impact and long-term trauma experienced by victims. Based on these findings, it is recommended that legal regulations be strengthened, particularly regarding sentencing enhancements for perpetrators from certain professions, improvement of evidentiary mechanisms, and integration of criminal sanctions with administrative and professional ethical sanctions. Accordingly, the sentencing system is expected to provide maximum protection for victims, create a deterrent.